Somalia - Debt Management Reform Plan - Hakim,Lea (Washington, DC: World Bank, 2022)
The Debt Reform Plan presented in this report was jointly developed with the authorities. It was based on a request for technical assistance from the Ministry of Finance given the achievement of HIPC decision point and the new opportunities for Somalia that are subsequently emerging. The Plan focuses on three core areas of debt management: the legal and institutional frameworks for debt management and debt reporting. The Debt Reform Plan is part of a broader set of institutional reforms on which Somalia is embarking and links to the broader PFM reform agenda. The reform activities are discussed in more detail in the report which is structured as follows: section two provides background on the macro-fiscal situation in Somalia. The report then delves into the three key areas reviewed in the TA providing sound practice, an overview of the current situation, and description of recommended action in each section. Section three covers the Legal Framework; section four Institutional Framework and section five Debt Recording, Reporting and Monitoring. A log-frame (Annex I) outlines the specific actions, sequencing, and expected outcomes for the overall proposed reform plan. The reform plan mission team is ready to provide input and feedback throughout the reform plan implementation phase.